STUDY OF THE TEAM DYNAMICS AND CONFLICTS RESOLUTION FOR ENHANCING COLLABORATION AND PERFORMANCE IN PROJECT MANAGEMENT - Muhammad Imran Khan,; Abdul Basit,; Dr. Fawad Ahmad,; Dr. Fazli Kareem,; Javed Saleem,; Dr. Muhammad Zeeshan Ahad, (Spectrum of Engineering Sciences, 2025)
Effective team dynamics, conflict resolution, and collaboration are crucial for the success of construction projects. Poor communication, lack of trust, and unresolved conflicts can lead to inefficiencies, delays, and cost overruns. Understanding these factors and identifying key elements that influence project performance can improve overall project outcomes. This research aims to examine the impact of team dynamics, conflict resolution strategies, and collaboration on construction project outcomes. The study identifies the most critical factors affecting team performance and provides recommendations for enhancing teamwork and conflict management. A mixed-method approach was used, incorporating both qualitative and quantitative data collection techniques. A structured questionnaire was developed based on an extensive literature review and expert interviews. Data was collected from construction professionals and analyzed using the Relative Importance Index (RII), Analytical Hierarchy Process (AHP), and Statistical Package for the Social Sciences (SPSS) to ensure comprehensive statistical validation. The results indicate that openness in communication (AHP eigenvalue: 0.2566, RII: 0.8407), confidence in roles (AHP eigenvalue: 0.3425, RII: 0.8237), and teamwork (AHP eigenvalue: 0.3408, RII: 0.8068) are the most influential factors in team success. Leadership through effective decision-making (AHP eigenvalue: 0.3365, RII: 0.8102) plays a vital role in achieving project goals. Among conflict types, interpersonal conflicts (AHP eigenvalue: 0.3529, RII: 0.8441) are the most critical and require structured resolution strategies. The study identifies compromise (AHP eigenvalue: 0.2523, RII: 0.8237) as the most effective conflict resolution approach. Moreover, conflict resolution directly impacts project outcomes (AHP eigenvalue: 0.3360, RII: 0.8203), influencing cost, time, and quality performance. Improving communication, fostering trust, and implementing structured conflict resolution strategies significantly enhance project outcomes in the construction sector. Training (AHP eigenvalue: 0.3397, RII: 0.8542) is found to be the most critical factor in enhancing collaboration. Effective communication (AHP eigenvalue: 0.3391, RII: 0.8441) ensures team alignment, while cost control (AHP eigenvalue: 0.3380, RII: 0.8237) plays a key role in maintaining budget efficiency. The study recommends promoting open communication, structured conflict resolution methods, and focused training programs to strengthen teamwork and collaboration, ultimately leading to better project performance. Keywords- (Team Dynamics, Conflicts Resolution For Enhancing Collaboration, Performance, Project Management).